Hialínocalcinosis litiásica de la vesícula biliar - Schneeberger, Federico; Aliano, Artigas; Maman de Goldstein, Perla; Montandon, Pablo (Cirugía del Uruguay, 1980)
Three cases of hyaline - calcinosis of the gallbladder _with cholelithiasis are reported. A brief summary of this patholgy is done and documents are added.